The Prudential Banking Principles in Providing Subsidized Housing Loans - Dora Kusumastuti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
The home ownership loans are one type of credit service provided by banks to customers who want special loans to meet the needs of home ownership. Credit disbursement by banks must be carried out with the principle of prudence (prudential banking), and must go through a careful analysis of the 5C's of Credit aspects, so that the loans that will be given can be returned on time. In reality, often loans that have been distributed to debtors become non-performing loans. This study discusses the implementation of the precautionary principle and the problems faced by banks in providing subsidized mortgages. This type of research is a normative juridical research with data sources from primary, secondary and tertiary legal materials. Using literature study as a collection technique. The results of this study explain that in implementing the prudential principle of banking in providing subsidized mortgage loans, the 5C's of Credit aspects are used. And in its implementation it uses Act No. 7 of 1992. There are obstacles in the implementation of the precautionary principle, starting from the various aspects of the character of the debtor, the uncooperativeness of the debtor and the mortgage house itself whose facilities are incomplete, causing a lack of interest from the public and the lack of socialization of the minimum period of use of subsidized housing.